Lymphopaenia at diagnosis of anti-neutrophil cytoplasmic antibody-vasculitis with renal involvement is correlated with severity and renal prognosis. Issue 6 (15th April 2021) - Wacrenier, Samuel; Riou, Jérémie; Jourdain, Pierre; Guibert, Fanny; Henry, Nicolas; Djema, Assia; Coindre, Jean-Philippe; Crochette, Romain; Cousin, Maud; Croue, Anne; Subra, Jean-François; Piccoli, Giorgina; et al.
Abstract: Background: Lymphopaenia is commonly observed in autoimmune diseases, where it has been associated with disease activity or prognosis. However, in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) only a few small-scale studies have been targeted towards this issue. Research has not yet focused on AAV with renal involvement (AAV-RI). Thus the aim of this study was to analyse the association between lymphocyte counts and outcomes in a large cohort of AAV-RI patients. Methods: We used the Maine-Anjou AAV registry that retrospectively gathers data on consecutive patients affected by AAV in four French nephrology centres, recorded since January 2000. We analysed clinical, biological and histological data at diagnosis of AAV-RI. Risk factors for end-stage kidney disease (ESKD) were analysed. Event-free survival was also assessed. Results: Among the 145 patients included in the study, those with lymphopaenia at diagnosis had a lower renal function at baseline [estimated glomerular filtration rate (eGFR) 13 versus 26 mL/min; P = 0.002] and were more likely to require kidney replacement therapy (51% versus 25%; P = 0.003). Lymphopaenia was correlated with histological lesions and especially with the percentage of sclerotic glomeruli (P = 0.0027). ESKD-free survival was lower in lymphopaenic patients (P < 0.0001). In multivariate Cox analysis, lymphopaenia was an independent risk factor for ESKD [hazard ratio 4.47 (95% confidence interval 2.06–9.72), P < 0.001]. Conclusions: Lymphopaenia correlates with the severity of AAV glomerulonephritis at diagnosis and predicts poor renal outcome. In this view, lymphopaenia could be used as a simple and cost-effective biomarker to assess renal prognosis at AAV-RI diagnosis.